2022
DOI: 10.1128/mbio.03343-21
|View full text |Cite
|
Sign up to set email alerts
|

A Feedback Regulatory Loop Containing McdR and WhiB2 Controls Cell Division and DNA Repair in Mycobacteria

Abstract: Drug-resistant M. tuberculosis poses a threat to the control and prevention of tuberculosis (TB) worldwide. Thus, there is a need to identify the mechanisms enabling M. tuberculosis to adapt and grow under drug-induced stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…S1 panels 2 nd day, 4 th day and 8 th day). Furthermore, the expression of the cell division checkpoint regulator of mycobacteria ( MSMEG_3644 ) that functions as a transcriptional activator of dnaE2 was also induced by ∼5 folds during biofilm formation (Table-2) 37 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S1 panels 2 nd day, 4 th day and 8 th day). Furthermore, the expression of the cell division checkpoint regulator of mycobacteria ( MSMEG_3644 ) that functions as a transcriptional activator of dnaE2 was also induced by ∼5 folds during biofilm formation (Table-2) 37 .…”
Section: Resultsmentioning
confidence: 99%
“…To understand the rationale behind this inconsistency we looked for potential regulators that could induce dnaE2 . A recent study has shown that over-expression of a MerR family transcription regulator Rv1830 (MSMEG_3644) acts as a mycobacterial cell cycle checkpoint by preventing mycobacterial cell division and simultaneously induces expression of dnaE2 and imuB 37 . Our RNA-Seq data revealed that the expression of MSMEG_3644 was induced by ∼5 folds in the biofilm stage but was repressed during the recovery stage (Table-2).…”
Section: Discussionmentioning
confidence: 99%
“…As we demonstrated that CvkR binding in P tnsB overlaps the TSS of P tnsB , and partially the -10 element, CvkR should regulate the expression of tnsB in a different way from cas12k . Actually, a few MerR-type regulators indeed have been reported to function as transcription repressors and regulate gene expression in significantly different ways, such as BldC 61 , HnoC 62 , and McdR 63 . BldC binds DNA direct repeats as cooperative multimers to regulate gene expression, while both HnoC and McdR are instances of regulators recognizing palindromic motifs overlapping TSS and -10 elements.…”
Section: Discussionmentioning
confidence: 99%
“…We even noticed a 20-nt long −10/−35 spacer in the promoter of one of the HnoC targets, hnoD , suggesting a possible similar regulatory mechanism of interfering with association of the RNAP holoenzyme and transcription initiation rather than reshaping of promoter DNA 62 . McdR, another MerR type repressor involved in controlling cell division, DNA repair, drug resistance and other stress responses in Mycobacteria, could also repress target promoters in this manner 63 . Moreover, the here investigated cyanobacterial CvkR shows 33% sequence identity with mycobacterial McdR (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…WhiB4 regulates b-lactamase expression, thus inducing antibiotic tolerance in M. tuberculosis (Mishra et al, 2017). WhiB2 is part of a regulatory loop involving rv1830 (mcdR) ultimately fine-tuning mycobacterial cell division and adaptation to stress response, including increased mutation rates during antibiotic challenge (Zhou et al, 2022). Recent genome-wide association analysis (GWAS) approaches have also identified novel associations between mutations in the whiB6 region and aminoglycosides resistance (Farhat et al, 2019).…”
Section: Whib Family (Whib1-7)mentioning
confidence: 99%